Legal framework for artificial intelligence - Tancer Verboten, Mojca (Acta Medico-Biotechnica, 2025)
Artificial intelligence is becoming a reality in today’s world, and is becoming increasingly integrated into our lives. The development of new technologies based on artificial intelligence is unprecedented, bringing numerous benefits and raising many legal questions. Its use can no longer be avoided; we must familiarize ourselves with it, take advantage of its benefits, and at the same time, be aware of the challenges it brings. The impact of artificial intelligence can be felt in all areas of the economy from manufacturing, public administration, transport, science, and education. It is also strongly present in some areas of healthcare. For its proper and safe use, it is necessary to define an appropriate legal framework that will lay the foundation for its proper functioning and resolve legal issues that arise in in the field of artificial intelligence.